DETERMINAN TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2014 - Adi Ardiyanto, 12.05.52.0202; Oktaviani, R. Meita (Students' Journal of Accounting and Banking, 2016)
Tax avoidance is mostly done by the taxpayer because it is legal. There are several factors, the Institutional Ownership, Proportion Of Independen Commissioners, Quality Audits, Committee Audits, ROA, Corporate Risk. This research was conducted at the companies listed on the Stock Exchange in the observation period 2012-2014. Sampling method used was purposive sampling method with a sample of 66 companies during the observation period fro 2012 to 2014 in a row for a total of 198 samples. Relationship and (or) influence between variable is described by using multiple regression analysis. Based on the results of multiple linear regression analysis, the results showed that the variables that affect negatively the committee audits, ROA, while the positive effect the proportion of independen commissioners, quality audit, and institutional ownership, the corporate risk not effect of tax avoidance that do manufacturing companies listed in Indonesia Stock Exchange observation period 2012-2014.Keywords: Institutional Ownership, Proportion Of Independen Commissioners, Quality Audits, Committee Audits, ROA, Corporate Risk, Tax Avoidance